Diversity and Uses of Tree Species in the Deciduous Dipterocarp Forest, Mae Chaem District, Chiang Mai Province, Northern Thailand - Larpkern, Panadda; Eriksen, Marit; Waiboonya, Panya (Naresuan University Journal: Science and Technology (NUJST), 2017)
This paper presents a study of tree species diversity of deciduous dipterocarp forest (DDF) in Mae Chaem District, Chiang Mai Province, northern Thailand and a review of traditional uses. The tree species diversity (diameter at breast height, DBH ≥ 5.0 cm) was surveyed in a 1-ha plot. We found 1,572 individuals, belonging to 25 tree species (23 genera and 18 families). Dipterocarpus tuberculatus , Shorea obtusa and Gluta usitata were the most dominant species in the forest. Trees generally showed high abundance in a small size class (DBH £ 10 cm), indicating a high potential for regeneration processes after past disturbances. The review of traditional knowledge on uses revealed that most species can be used for different purposes, depending on species and culture. In conclusion, conserving this DDF should focus on maintaining tree species diversity by preventing severe fire and unsustainable uses. Keywords: Deciduous dipterocarp forest, Disturbances, Diversity, Forest regeneration, Traditional uses
Keywords: Deciduous dipterocarp forest; Disturbances; Diversity; Forest regeneration; Traditional uses